Hippo signaling interactions with Wnt/β-catenin and Notch signaling repress liver tumorigenesis - Kim, Wantae (J Clin Invest, 2016)
Malignant tumors develop through multiple steps of initiation and progression, and tumor initiation is of singular importance in tumor prevention, diagnosis, and treatment. However, the molecular mechanism whereby a signaling network of interacting pathways restrains proliferation in normal cells and prevents tumor initiation is still poorly understood. Here, we have reported that the Hippo, Wnt/β-catenin, and Notch pathways form an interacting network to maintain liver size and suppress hepatocellular carcinoma (HCC). Ablation of the mammalian Hippo kinases Mst1 and Mst2 in liver led to rapid HCC formation and activated Yes-associated protein/WW domain containing transcription regulator 1 (YAP/TAZ), STAT3, Wnt/β-catenin, and Notch signaling. Previous work has shown that abnormal activation of these downstream pathways can lead to HCC. Rigorous genetic experiments revealed that Notch signaling forms a positive feedback loop with the Hippo signaling effector YAP/TAZ to promote severe hepatomegaly and rapid HCC initiation and progression. Surprisingly, we found that Wnt/β-catenin signaling activation suppressed HCC formation by inhibiting the positive feedback loop between YAP/TAZ and Notch signaling. Furthermore, we found that STAT3 in hepatocytes is dispensable for HCC formation when mammalian sterile 20–like kinase 1 and 2 (Mst1 and Mst2) were removed. The molecular network we have identified provides insights into HCC molecular classifications and therapeutic developments for the treatment of liver tumors caused by distinct genetic mutations.